Perilaku Konsumen dalam Pengambilan Keputusan Pembelian secara Online melalui Platform TikTok Shop - Afrienza, Rizaldo; Mutmainah, Isbandriyati; Rumna, Rumna (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to analyze the influence of switching costs, reputation, and transaction convenience on purchasing decisions, with trust as a moderating variable. The population of this study were consumers who make shopping transactions through the TikTok platform. The sample used in this study was 131 respondents, collected using a non-probability sampling method, namely accidental sampling. The analytical methods used were multiple linear regression and Moderating Regression Analysis (MRA). The results of statistical tests with multiple linear regression analysis showed that, of the three independent variables, only the transaction convenience variable had a significant effect on purchasing decisions, while the switching cost and reputation variables were proven to have no significant effect. The results of statistical tests with Moderating Regression Analysis showed that the trust variable was able to strengthen the influence of switching costs and reputation on purchasing decisions, but was unable to moderate the effect of transaction convenience on purchasing decisions.